EKSPLORASI MORFOLOGI DAN KANDUNGAN PROKSIMAT PADA UBI JALAR (Ipomoea Batatas L.) DARI KEPULAUAN KEI, MALUKU - Bugis, Putri Aini; Raharjo, Simon Hadi Teguh; Wahditiya, Andi Adriani (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
The objective of this study was to determine the most distinguishing morphological characteristics among several accessions of sweet potato (Ipomoea batatas L.) and to measure the water, ash, protein, fat, and carbohydrate content in each accession. The research methods included land preparation, preparation of four types of sweet potato colors ready for planting, planting, morphological observations, and harvesting. The study was conducted in Ohoitahit Village, North Dullah Island District, Tual City, Kei Islands, Maluku. The results showed that there were four types of sweet potato accessions with various morphological characteristics. Each accession showed significant diversity in stem length, leaf shape, and tuber shape. These observations indicate that morphological diversity among accessions can be used as the main distinguishing parameter. Proximate analysis showed variation in water, ash, protein, fat, and carbohydrate content among the four sweet potato accessions. This data provides important insights into the agronomic potential and nutritional value of sweet potatoes from the Kei Islands, which can be used for the development of superior varieties and further utilization in the food industry. This research also reinforces the importance of conservation and utilization of local biodiversity in supporting regional food security.